Contribuições para a micropropagação de Peltophorum dubium (Sprengel) Taubert - Curti, Aline Ritter (2011)
Peltophorum dubium (Sprengel) Taubert is a native forest species that shows fast development with environmental and economic importance. However, studies related to the production of quality seedlings by vegetative propagation are still incipient. As a result, this study investigated methods for multiplication and in vitro root formation of Peltophorum dubium. For multiplication was evaluated the use, alone or combined, of the cytokinins 6-Benzylaminopurine (BAP), Kinetin (KIN), isopentenyladenine (2iP) and Thidiazuron (TDZ) in different concentrations and its association with the auxin alpha-naphthalene acetic acid (ANA) or activated charcoal. In the formation of roots were evaluated the auxins NAA, indole-3-butyric acid (IBA)and 2,4-dichlorophenoxyacetic acid (2,4-D) at different concentrations and the exposure time of shoots to these growth regulators and their cultivation in nutrient media MS and WPM. We evaluated also alternative substrates (vermiculite, Plantmax ® or fine sand) associated with different volumes of MS nutrient medium containing agar or not, in the in vitro root formation, with the aim of providing a more porous medium to the development of root system. There wasn t emission of adventitious shoots in the absence of cytokinins in epicotyls of Peltophorum dubium. TDZ and 2iP, at 5 or 10 μM, associated with 0.015 μM NAA in MS medium promoted the highest percentage of buds. However, the shoots showed little development, intensive formation of callus at the base and leaf chlorosis, which didn t permit its use. In the absence of cytokinin was not observed leaf chlorosis. The inclusion of 1 g L-1 of activated charcoal to the nutrient medium MS provided more vigorous shoots and the use of epicotyl containing cotyledonary nodes allowed the formation of new shoots in all treatments. When BAP was used alone was not observed the emission of adventitious buds on epicotyl; these only started to occur when we used combinations of BAP with KIN or 2iP. In MS nutrient medium, the highest callus formation was observed in the presence of 10 μM IBA, after 30 days. In nutrient medium WPM, the highest callus formation occurred in the absence of IBA. Reduced percentage of root formation in Peltophorum dubium shoots were both obtained in MS medium as in WPM, regardless of the absence or presence of IBA. In MS nutrient medium, regardless of the presence or absence of auxin and independent of the concentration of this class of growth regulators, callus formation occurred at the base of the shoots of Peltophorum dubium to 30 days in vitro culture. Both the nutrient media MS and WPM possibilite the formation of roots on shoots of Peltophorum dubium with the use of "pulse" treatments of IBA at concentrations between 0 and 20 μM for six days in nutrient medium. However, the root formation was not satisfactory. There was intense callus formation at the base of the shoots at 60 days of culture, when the vermiculite was used as substrate in the process of inducing rooting. At 60 days it was possible to obtain root formation on all substrates. The combination of MS medium supplemented with 10 μM IBA, vermiculite and agar provided 36.8% of root formation in shoots, as well as improved the quality of roots of Peltophorum dubium. The use of epicotyl containing cotyledonary nodes on MS nutrient medium, supplemented with activated charcoal reduces the callus at the base of the explants and raises the emission of adventitious shoots for 75% and provides the obtaining of more vigorous shoots and leaves without chlorosis. The auxins NAA, IBA and 2,4-D in concentrations of up to 20 μM during the whole period of culture are not efficient in promoting the in vitro formation of roots on shoots of Peltophorum dubium. The use of pulse treatment with IBA for six days and the reduction the concentration of salts from the nutrient medium after this period allows the formation of roots, independent of IBA concentration and use of MS or WPM media. Most promising results are obtained using the combination of vermiculite, nutrient medium and agar, both in percentage of root formation, and the quality of root system formed.